Special place, interesting times : the island of Palagruža and transitional periods in Adriatic prehistory - Forenbaher, Stašo (Archaeopress Publishing Ltd, 2018)
Palagruža is a remote Croatian archipelago in the middle of the Adriatic Sea, unexpectedly abundant in high-grade archaeological evidence, dating precisely from the three periods of later Adriatic prehistory marked by radical change. This book explores the archaeology and history of Palagruža.